(untitled) (Revista LIDER, 2020)
In the last decades, the world has been witness to significant technological and productive changes that have altered the dynamics of the capitalist system. The global economy is entering a new production fase called postfordism, in which knowledge has become the most important factor in the productive activity. In this context, in which ideas have an important role in the productive activities, the territories try to build instruments to generate or attract knowledge. Among the instruments to achieve this objective are technology parks. These are iniciatives implemented by local communities in order to extend the economic base of high tech industries in a territory. The present work pretends to analize the dynamics of a particular park, called the litoralcentro technology park which is situated in Santa Fé-Argentina.